A new species of the genus Triplophysa (Cypriniformes: Nemacheilidae), Triplophysa longliensis sp. nov, from Guizhou, China - Ren, Qiu; Yang, Jun-Xing; Chen, Xiao-Yong (Zootaxa, 2012)
A new species of nemacheilid loach, Triplophysa longliensis, is described from Yudonghe River, a small tributary of PearlRiver in Guizhou Province, China. It can be distinguished from other valid Triplophysa loaches by the followingcombination of characters: body smooth and scaleless; head tapering; lips thin and smooth; posterior chamber of gasbladder highly developed, long, bag-shaped, tip reaching origin of pelvic fin; intestine short, bending in zigzag shapebehind stomach; insertion of pelvic fin posterior to dorsal-fin origin; dorsal-fin origin closer to snout tip than to caudalfin base; caudal fin deeply forked, upper lobe obviously longer than lower one; pelvic-fin tip reaching to anus.